Strategi Pemasaran di GraPARI Telkomsel Cabang Kota Malang - Zahro Ilbatul, Fatimatuz; Sinollah (Jurnal Bisnis Islam dan Kewirausahaan, 2024)
Facing intense competition for similar services, GraPARI Telkomsel branch Jl. Letjen S. Parman No. 47 Purwantoro, Blimbing District, Malang City implements a marketing strategy through SWOT analysis by analyzing the internal and external environment. The aim of this research is to find out the right competitive strategy based on SWOT analysis. (Strengths, Weaknesses, Opportunities, Threats) which is implemented at GraPARI Telkomsel branch Jl. Letjen S. Parman No. 47 Purwantoro, Blimbing District, Malang City. The data collection method used by the author is observation and interviews to obtain primary data and secondary data, with descriptive analysis discussion techniques. Based on the SWOT Analysis Results, GraPARI Telkomsel branch Jl. Letjen S. Parman No. 47 Purwantoro, Blimbing District, Malang City is in the Strength-Opportunity Strategy (SO Strategy) position. This strategy uses internal strengths to make the most of opportunities. The results of the research above are the reason for providing advice that GraPARI Telkomsel branch Jl. Letjen S. Parman No. 47 Purwantoro, Blimbing District, Malang City needs to carry out an internal and external environmental analysis process considering the tight competition between companies with similar products